No relationship between gender stereotypes and mental rotation in preschool girls - Ebert, W. Miro; Jost, Leonardo; Jansen, Petra (Frontiers in Psychology, 2025)
Gender stereotypes about spatial ability have been proposed as a contributing factor to the gender gap in STEM. This goal of this study was to investigate whether implicit gender stereotypes regarding spatial ability are associated with mental rotation (MR) performance in preschool-aged girls, and whether visuospatial working memory (VSWM) plays a moderating role. Fifty-two girls aged 5 to 6.75 years completed a chronometric MR task, a computerized Corsi block-tapping task (assessing VSWM), and a single-target Implicit Association Test measuring associations between gender and toys used in spatial play. Participants did not show significant implicit stereotypes favoring either gender. Contrary to our hypotheses, no evidence for a relationship between implicit stereotypes and MR response times was found. Unexpectedly, stronger implicit associations linking boys with spatial ability were associated with higher MR accuracy. VSWM was positively correlated with both MR accuracy and implicit stereotype scores. Since the hypothesized relationship between implicit stereotypes and MR was not observed, a potential moderation through VSWM was not examined. Our findings diverge from prior research suggesting that stereotype-consistent associations in girls are linked to lower spatial task performance. Taken together, the results cast doubt on the robustness of implicit gender stereotypes about spatial ability in early childhood and highlight the complexity of their potential impact on spatial cognition. Further research is needed to clarify under what conditions, if any, such stereotypes affect performance in young children.